Extension for Community Healthcare Outcomes—Care Transitions: Enhancing Geriatric Care Transitions Through a Multidisciplinary Videoconference. Issue 3 (29th December 2016) - Farris, Grace; Sircar, Mousumi; Bortinger, Jonathan; Moore, Amber; Krupp, J. Elyse; Marshall, John; Abrams, Alan; Lipsitz, Lewis; Mattison, Melissa
Abstract : Objectives: To examine whether a novel videoconference that connects an interdisciplinary hospital‐based team with clinicians at postacute care sites improves interprofessional communication and reduces medication errors. Design: Prospective cohort. Setting: One tertiary care medical center and eight postacute care sites. Participants: Hospital‐based providers (hospitalists, geriatricians, pharmacists, social workers, medical trainees, and subspecialists) and postacute care clinicians. Intervention: All patients discharged to eight postacute care sites were discussed in a weekly videoconference. Measurement: Preliminary data including demographic characteristics of the patients discussed, postacute care provider satisfaction survey results, and data on medication errors are reported. Results: Over 2 years, 907 patients were discussed; 84.6% were discussed with staff at subacute skilled nursing facilities and the remainder with clinicians at one long‐term acute care facility. They had an average hospital length of stay of 6.8 days. Postacute care providers felt that the videoconference enhanced communication and provided much‐needed access to information and hospital staff. Of the 106 pharmacy discrepancies identified, 16% involved an omission of a medication. Conclusion: As increasing numbers of older adults are discharged to postacute care facilities, they face high‐risk care transitions. Extension for Community Healthcare Outcomes—Care Transitions (ECHO‐CT) facilitates interdisciplinary communication between hospital and postacute care providers, who normally have minimal interaction. Preliminary data suggests that ECHO‐CT may improve the transitions of care processes between these sites.